Secondary Level Students’ Choice of Learning Styles in Nepalese English as a Second Language Classrooms - Baral, Parmeshor (Journal of TESON, 2022)
Many research studies agreed that learning is an idiosyncratic process since individual learner possesses a unique style of learning. This research is an attempt to investigate the learning style students in grades 11 and 12 employ in learning academic and nonacademic texts. For the same, 10 students from five higher secondary schools were chosen as the sample for the study using a judgmental sampling procedure. Semistructured interviews were conducted, and data were analyzed descriptively. The findings suggest that learning style depended on the type of texts they learned and the time-bound contexts of learning. In this, it was identified that each of the learners shifted from creative learning to rote learning when they needed to prepare for the examination.